Redescription and a new record of Centrophthalmus sinensis Raffray, 1904(Coleoptera: Staphylinidae: Pselaphinae) - Feng, Ting; Yin, Zi-Wei (Zootaxa, 2023)
A new record of Centrophthalmus sinensis Raffray, 1904 from Suzhou, East China is provided, which is also the first Pselaphinae known to occur in this city, and the third pselaphine species from Jiangsu Province. A redescription of the species is given, aided with illustrations of the habitus and other morphological details.